Complete framework for tau polarimetry in B→D(*) τν decays - Asadi, Pouya; Hallin, Anna; Martin Camalich, Jorge; Shih, David; Westhoff, Susanne (Physical review, 2020)
The meson decays B→Dτν and B→D∗τν are sensitive probes of the b→cτν transition. In this work, we present a complete framework to obtain the maximum information on the physics of B→D(*)τν with polarized τ leptons and unpolarized D(*) mesons. Focusing on the hadronic decays τ→πν and τ→ρν, we show how to extract seven τ asymmetries from a fully differential analysis of the final-state kinematics. At Belle II with 50 ab−1 of data, these asymmetries could potentially be measured with percent-level statistical uncertainty. This would open a new window into possible new physics contributions in b→cτν and would allow us to decipher its Lorentz and gauge structure.
Gesehen am 21.01.2021